Income inequality : regional analyses within a human capital framework - Chiswick, Barry R. (New York : National Bureau of Economic Research : distributed by Columbia University Press, 1974)
This book deals with distribution of income as it relate to investment in human capital
Includes bibliographical references: p. 199-204.
oo 18/10/2018
Loans
Keywords: Income distribution; Human capital